Determination of neonicotinoid insecticides on stingless bee, Trigona itama through filter paper bioassay method - Mahamed, Aisyah (2018)
In Malaysia, stingless bee is known as Kelulut. They are the common visitors to flowering plants and an important pollinators of crops. Nowadays, many farmers are relying on pesticide to protect their crop. The pesticide could be exposed to pollinators during application through drift and contact residue from ingestion of pollen and nectar. In Malaysia, there are no study has been reported on the effect of pesticide on meliponiculture. Therefore, the objective of this study is to evaluate the sensitivity of stingless bee to the insecticide through filter paper disc bioassay. Through this research, information of the lethal toxicity of insecticide to the stingless bee was found and be use as future references. Bioassay was conducted on T. itama to identify the LC50 (in ppm value) of thiamethoxam and imidacloprid insecticides. Four concentrations of each insecticides and a control were prepared, each concentration has four replications with 10 T. itama. The insecticides serial dilutions were prepared from commercial formulation. The data recorded for the number of bees survive after 24 and 48 hours of experiments. The LC50 was determined by using Probit Analysis (EPA Probit Ver 1.5 software). The LC50 of imidacloprid for 24 and 48 hours are 13.967 ppm and 7.183 ppm respectively. The LC50 of thiamethoxam for 24 and 48 hours are 25.253 ppm and 18.444 ppm respectively. Thus, imidacloprid is highly toxic compared to thiamethoxam.